2009
DOI: 10.5026/jgeography.118.955
|View full text |Cite
|
Sign up to set email alerts
|

Geotechnical Properties of Core Samples Recovered from Seabed Ground in East Nankai Trough

Abstract: To produce methane gas from methane hydrate safely and without damaging the environment, we need to address many wide-ranging environmental issues. One is to assess seabed deformation during methane gas production. We are investigating if deformation of seabed ground occurs during the production of methane gas from methane hydrate. Geotechnical properties of seabed ground have significant effects on deformation behavior. Soil samples were recovered from the East Nankai Trough where there is expected to be a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…They conducted one-dimensional consolidation testing on the sediments recovered by the advanced piston corer and extended core barrel in the drilling and coring program conducted in 2004 by MH21 (2001). The results of our study were in the same range as those of Nishio et al (2009). Thus, the permeability, which is an important parameter for reservoir simulation, can be obtained from the consolidation process in a triaxial compression test.…”
Section: Consolidation Testingsupporting
confidence: 52%
See 2 more Smart Citations
“…They conducted one-dimensional consolidation testing on the sediments recovered by the advanced piston corer and extended core barrel in the drilling and coring program conducted in 2004 by MH21 (2001). The results of our study were in the same range as those of Nishio et al (2009). Thus, the permeability, which is an important parameter for reservoir simulation, can be obtained from the consolidation process in a triaxial compression test.…”
Section: Consolidation Testingsupporting
confidence: 52%
“…These results are plotted in Figure 5, and show that the clayey-silty sediments have permeability values of approximately tens of microdarcies, as shown by the solid circles; the permeability decreases with increasing depth. Nishio et al (2009) reported that the permeability of clayey-silty sediments in the Nankai Trough was 10e100 mD. They conducted one-dimensional consolidation testing on the sediments recovered by the advanced piston corer and extended core barrel in the drilling and coring program conducted in 2004 by MH21 (2001).…”
Section: Consolidation Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…A pre-drilling campaign conducted during 2012 for evaluating the production feasibility from marine sediments confirmed the presence of 60 m thick NGH bearing sediments in the northern slope of Daini Atsumi Knoll in eastern Nankai Trough (Fujii et al, 2013). Subsequently, wells were drilled and pressure core samples were collected for evaluating the reservoir characterization and production (Nishio et al, 2013). They included one production well, two monitoring wells, spatially distributed sea bed based instrumentation for temperature and seismic measurements.…”
Section: Natural Gas Hydratementioning
confidence: 99%
“…The subsidence could also lead to destabilization of the well bore (Rutqvist et al, 2012). Collections of site specific samples (Ramesh et al, 2015), geo technical modeling (Rutquist and Moridis, 2007)and an experimental analysis (Nishio et al, 2013) on the samples are required to be carried out, to determine the post dissociation behavior of the formation so as to have a reliable well design, and to identify the practical reach of a well and other geo technical limitations. Field scale experiments shall also be required to validate the subsidence model results, for which precise distributed sea bed subsidence measurement systems are required, which are similar to the measurement strategies reported during the Nankai Trough field scale studies (Saeki, 2014).…”
Section: Well Reach Limitationsmentioning
confidence: 99%